Airport Factor in Flight Delays in Indonesia - Setiawan, Indra; Majid, Suharto Abdul; Yuliantini, Yuliantini (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2015)
Airport is a vital subsystem in the air transport system which has an important and strategic role in smoothening air traffic, so that an airport must be designed to be always ready in all situations and conditions to serve airline flights securely, orderly, smoothly, and quickly. The frequent delay faced by Indonesian domestic scheduled airlines is not fully caused by internal factor of the companies. Instead, it can be caused by the airport factor. The problems faced by airports in Indonesia which have impacts on the performance of flight punctuality among other things are capacity, slot time, quality of flight navigation devices, accessibility, professionalism of airport and ATC human resources, infrastructure, facilities, equipment, and the human resources handling security and safety of flights in airport. This article recommends that an in-depth study should be carried out to map the interrelations between the airport factor in the flight delay related to facilities integration and the airport authority in the flight activities in Indonesia. Key Words: airport, factor, flight delay and issue of development